1999
DOI: 10.1515/cclm.1999.011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Hemoglobin-Based Oxygen Carrier HBOC-201 on Laboratory Instrumentation: Cobas Integra, Chiron Blood Gas Analyzer 840, Sysmex™SE-9000 and BCT

Abstract: As part of a clinical trial, we evaluated the effects of the hemoglobin-based oxygen-carrier (HBOC) HBOC-201 (an ultrapurified, stroma-free bovine hemoglobin product, Biopure, Cambridge, MA, USA) on our routine clinical chemistry analyzer (Cobas Integra, F. Hoffmann-La Roche Ltd, Basel, Switzerland ), blood gas analyzer (Chiron 840, Chiron Diagnostics Corporation, East Walpole, MA, USA), routine hemocytometry analyzer (Sysmex SE-9000, TOA Medical Electronics Co Ltd., Kobe, Japan), hemostasis analyzer (BCT, Dad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 7 publications
0
21
0
2
Order By: Relevance
“…Recently, a set of therapeutic haemoglobin derivatives (so-called HBOC = haemoglobin-based oxygen carriers) that have been developed as blood substitutes, and appearing in concentrations of up to 50 of the patients are handled as described in specific literature references [14,15,16]. These materials import strong red colour to plasma and serum.…”
Section: Sample Appearing As Haemolytic Caused By Therapeutic Haemoglmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a set of therapeutic haemoglobin derivatives (so-called HBOC = haemoglobin-based oxygen carriers) that have been developed as blood substitutes, and appearing in concentrations of up to 50 of the patients are handled as described in specific literature references [14,15,16]. These materials import strong red colour to plasma and serum.…”
Section: Sample Appearing As Haemolytic Caused By Therapeutic Haemoglmentioning
confidence: 99%
“…Therapeutic haemoglobin derivatives yield a visible haemoglobin concentration within the range of 10 -50 g/L, with an absorption spectrum indistinguishable from natural haemoglobin [14,15,16,22,23]. However, since haemoglobin concentrations of this magnitude rarely occur in vivo, the use of therapeutic haemoglobin derivatives is to be assumed at this plasma haemoglobin concentration.…”
Section: Identification Of Haemoglobin Derived Oxygen Carriersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent study found significant, albeit transient, increases in total peripheral resistance, systolic, diastolic, and mean arterial blood pressure, and decreases in heart rate, cardiac index and oxygen delivery in patients receiving the solution 16 . In addition, Wolthius and colleagues 17 reported that HBOC-201 confounds the laboratory detection of a number of serum components, including direct bilirubin, the MB fraction of creatine kinase, and magnesium. Kasper et al…”
Section: Hemoglobin Solutionsmentioning
confidence: 99%
“…The same laboratory interference instructions were conveyed to each institution by electronic documents to the laboratory director and phone briefings or e-mails to the attending clinician in charge of the patient's care, indicating that HBOC-201 in the plasma caused interferences with colorimetric laboratory and clinical measurements. [35][36][37] The FDA gave individual patient approval, not as a CU protocol, so physiologic and laboratory data collection was not consistent across patients or the 49 CU sites, although specific common data items necessary to patient care and use of the product were recorded. Pretreatment data were collected 0.5 to 0.25 hours preceding, and closest to, the initial HBOC-201 infusion.…”
mentioning
confidence: 99%